New Coordination Compounds Based on Cd(NCS)2(4‐Ethylpyridine)x (x = 4, 2, 1). Issue 2 (31st January 2013) - Wöhlert, Susanne; Jess, Inke; Näther, Christian
Abstract The reactions of different ratios of cadmium(II) thiocyanate and 4‐ethylpyridine as neutral co‐ligand in water at room temperature leads to the formation of the three new coordination compounds of different topology. In the crystal structure of the 1:4 compound (1:4 = ratio between metal and neutral co‐ligand) Cd(NCS)2(4‐ethylpyridine)4 (1) discrete complexes are found, in which the cadmium ions are coordinated by two terminal N‐bonded anionic ligands and four 4‐ethylpyridine co‐ligands. In the crystal structure of the 1:2 compound [Cd(NCS)2(4‐ethylpyridine)2]n (2) the cadmium cations are coordinated by two S‐bonded, two N‐bonded thiocyanato anions and two 4‐ethylpyridine ligands, all of them are trans‐oriented. The Cd2+ cations are connected by μ‐1, 3 bridging thiocyanato anions into chains, which elongate in the direction of the crystallographic a axis. In the crystal structure of the 1:1 compound [Cd(NCS)2(4‐ethylpyridine)]n (3) a more condensed coordination network is observed, in which each Cd2+ cation is coordinated by two N‐bonded and three S‐bonded as well as one 4‐ethylpyridine ligand within slightly distorted octahedra. The cadmium cations are linked into chains by μ‐1, 3‐ and μ‐1, 1, 3‐bridging thiocyanato anions. On heating the 1:4 compound 1 two mass steps are observed in the TG curve, of which the first one is well resolved. The residue obtained after the first TG step is investigated by XRPD, elemental analysis, and IR spectroscopy, it is proven that the 1:2 compound Cd(NCS)2(4‐ethylpyridine)2 is obtained as a phase pure material. Based on the results of IR spectroscopic investigations the coordination mode of the thiocyanato anions was additionally investigated.